Prayer service at First Unitarian Church - Ted Sahl (photographer):::Creator::::::::::::
Photograph shows Reverend Troy D. Perry leading a prayer service at the First Unitarian Church in San Jose, 1979. The people there are standing with their hands clasped and raised. They appear to the singing.